Macroalgae-Fortified Sausages: Nutritional and Quality Aspects Influenced by Non-Thermal High-Pressure Processing - Catarina Marçal; Carlos A. Pinto; Artur M. S. Silva; Carla Monteiro; Jorge A. Saraiva; Susana M. Cardoso (Foods, 2021)
The present work evaluated the nutritional impact of macroalgae flours used as new ingredients in fermented sausages and the feasibility of using high-pressure processing (HPP) as a non-thermal pasteurization methodology to keep the quality attributes of the new food products. A commercial macroalgae mix was used in the formulation of new macroalgae-fortified meat frankfurter sausages (F-MFS), macroalgae-fortified vegetable frankfurter sausages (F-VFS) and in macroalgae-fortified traditional Portuguese sausage “chouriço” (F-TPS), overall incrementing the contents of Mg, K, Ca, Mn and Fe and decreasing the Na/K ratio. The application of HPP allowed extending the shelf-life of frankfurters by about 3-fold and improved the safety of “chouriço” along 180 days of storage, keeping its microbial load below the detection limit. The prevention of microbial growth in F-MFS and F-VFS was accompanied by pH stability of the products. In addition, no significant detriment on surface color and fatty acids was observed between pressurized and non-pressurized sausages, allowing consolidating the suitability of HPP in seaweed-fortified fermented sausages.